Montrer pour cacher : la transmission d’un savoir rituel shuar (Amazonie équatorienne) dans le contexte néo-chamanique - Katarzyna Zajda (Nuevo mundo - Mundos Nuevos, 2017)
Contemporary Shuar shamanism is characterised by, on the one hand, its plasticity and its adaptability to new contests and, on the other hand, by heterogeneity of its clientele, which now includes an increasing number of Western patients. In the absence of a shared system of representations and with the necessity for an explanatory discourse, in these ‘neo-shamanic’ rituals inspired by New Age religion, the shaman occupies a paradoxical position. From his point of view, the effectiveness of an intervention rests on the traditional obligation of silence. The experience of shamanism is too complex, intense and multi-sensory to be easily describable and should thus remain secret. But for the shamans’ European patients his efficacy depends, on the contrary, on an aptitude for explicating their experiences. We will describe the interactions among the different participants in order to show how the shaman, by means of simple speeches which frequently take up the propositions of those he addresses, transposes, in a discursive register, the acts of mystification which have been reported, in the context of traditional shamanic practice, in the manipulation of objects. It is thus a dissimulation that hides its own secret.